Scaling climate smart coffee and cocoa - Rainforest Alliance (2018)
Key lessons from using Certification as scaling mechanism for CSA under the CCAFS funded Climate Smart Coffee and Cocoa Value Chain Project (CSVC) Outcome 1: Influence on new Rainforest Alliance (RA) standard development Outcome 2: UTZ/RA SP application and scaling Outcome 4: Landscape work